Twenty‐First‐Century Climate Education: Developing Diverse, Confident, and Competent Leaders in Environmental Sustainability. Issue 2 (3rd February 2020) - Halliwell, Philip; Whipple, Sarah; Hassel, Kelly N.; Bowser, Gillian; Husic, Diane White; Brown, Mark A.
Abstract: With climate change impacting systems globally at alarming rates, the need for educating the next generation of environmental stewards is necessary. The Rocky Mountain Sustainability and Science Network (RMSSN) is an immersive field experience for undergraduate and graduate students interested in climate change and sustainability within National Parks. The program was established to educate and cultivate a diverse audience of future leaders, environmental guardians, and sustainability advocates with a focus on engaging underrepresented minorities (URM) in science. Participants were evaluated through efficacy instruments and focus groups to determine how a short‐term research experience could impact a student's future outlook and perceived ability to impact science and sustainability. Findings indicate URM, and majority students were more confident in their abilities, and more motivated to continue within their studies. RMSSN provides a framework that is translatable to other field‐based curriculums. This paper addresses specific engagement mechanisms for educating future science leaders.